Highly Fluorescent Merocyanine and Cyanine PMMA Copolymers. Issue 15 (20th June 2018) - Pasch, Peter; Papadopoulos, Julian; Goralczyk, Andreas; Hofer, Marc L.; Tabatabai, Monir; Müller, Thomas J. J.; Hartmann, Laura
Abstract: Polymerizable merocyanine and cyanine dye monomers are synthesized and applied in a statistical copolymerization with methylmethacrylate, giving a series of highly fluorescent poly(methyl methacrylate) (PMMA) copolymers. Photophysical properties of yellow to red merocyanine‐ and of pink to dark purple cyanine‐containing copolymers are studied by fluorescence spectroscopy in solid state as well as in different solvents. The highest quantum yield measured in the solid state is observed for copolymers with the lowest dye content: 16% for merocyanine‐based and 13% for cyanine‐based copolymers, respectively. Fluorescence properties in solution show positive solvatochromism for both merocyanine monomer and copolymer. Copolymer, in comparison to monomer, is hypsochromically shifted to lower wavelengths which point toward H‐aggregation of the chromophores in the copolymer matrix. Abstract : Polymerizable merocyanine and cyanine dyes are synthesized and used in copolymerization with methyl methacrylate, giving a series of highly fluorescent poly(methyl methacrylate) copolymers. Fluorescent properties are investigated in the solid state as well as in solution, showing the effects of copolymer dye incorporation upon fluorescence quantum yields and solvatochromism.